The simplified expression is -9a -9b.
There are 3 terms in the given expression of 6a+9b+15
9b + 6 - 8 = -36 9b = -38 b = 4.2222222(repeating)
You would factor 3a + 9b as: 3(a+3b)
2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4
3A + 9B = 3(A + 3B)
The simplified expression is -9a -9b.
There are 3 terms in the given expression of 6a+9b+15
9b + 6 - 8 = -36 9b = -38 b = 4.2222222(repeating)
10b
You would factor 3a + 9b as: 3(a+3b)
(6ab + 9b)/(2a + 3) = 3b(2a + 3)/(2a + 3) = 3b
2a + 3 - 9b - a - 7 Bring like terms together: = 2a - a - 9b + 3 - 7 Combine like terms: = a - 9b - 4
-28am + 17b
3a + 5b - 6a - 9b = -3a - 4b
the answer is 7b over 9b because the rule is numbers now letters later
4a+2b-1a+9b combine all alike variables using commutative property of addition 4a-1a+2b+9b Then add the like variables 3a+11b